Propagable Optical Vortices with Natural Noninteger Orbital Angular Momentum in Free Space - Xiaoyu Weng; Yu Miao; Guanxue Wang; Qiufang Zhan; Xiangmei Dong; Junle Qu; Xiumin Gao; Songlin Zhuang (Advanced Photonics Research, 2023)
Light beams with optical vortices can propagate in free space only with integer orbital angular momentum. Herein, this scientific consensus theoretically and experimentally is upheaved by proposing light beams carrying natural noninteger orbital angular momentum. These peculiar vortex beams are unique solutions to the Helmholtz equation, which possesses optical vortices with topological charges of l + 0.5, where l is an integer. During propagation in free space, their amplitudes and vortex phases with noninteger topological charges can be maintained stably. The findings of this study provide an alternative state of optical vortices in physics, which can serve as basis for innovations in optics and related scientific fields.